Mapping Difference: Critical Connections between Crip and Diaspora Communities - Chandler, Eliza (Critical Disability Discourses, 2013)
This paper explores connections between crip and diaspora communities. I begin by discussing how the cultural production of racialized and disabled people are not analogous, but, rather, entangled. Following this, I reflect on a monologue by Leah Lakshmi Piepzna-Samarasinha that articulates the knot between the production of land and the production of disability. I then discuss how our understanding of geography is related to our understanding of the people who are placed or place themselves in particular geographic sites. I use Jasbir Puar’s concept of “debility” (2011) to unpack how the material and discursive production of people and land as disposable are also knotted. This paper ends by reflecting on how “unworking” (Walcott, 2003) our understandings of community and disability, the relationship between place and people, is one way of recognizing the “different stories of differences,” stories that challenges the mainstream disability right movement’s understanding of disability. Keywords: community; geography; diaspora; debility; environmental racism; biopolitics; neoliberalism